Emil Law Enforcement Of Fishery Crimes By Corporations In Indonesia: Law Enforcement Of Fishery Crimes By Corporations In Indonesia - Emiel Salim Siregar; Adi Mansar; Surya Perdana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This article aims to enforce the law on criminal acts of fisheries by corporations in Indonesia. Fisheries is a leading sector for the Indonesian economy, but there are often violations of the law committed by corporations in their fisheries activities, so that law enforcement against criminal acts of fisheries by corporations in Indonesia has complex challenges. This study uses normative legal research, which refers to applicable legal regulations and binds the surrounding community. This study formulates critical questions about the legal regulation of criminal acts of fisheries by corporations in Indonesia and also the implementation of law enforcement of criminal acts of fisheries by corporations in Indonesia. Increasing cooperation between government law enforcement agencies and civil society is important to overcome existing challenges and ensure the sustainability of fisheries resources in Indonesia.